2006
DOI: 10.1002/pssa.200521142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an external mechanical strain on the character of the magneto‐electric effect in epitaxial films of yttrium iron garnet

Abstract: Epitaxial films of yttrium iron garnet (YIG) exhibit electric‐field‐dependent magnetic properties that have been experimentally measured as a function of the applied magnetic field and as a function of strain. The laser polarimeter technique was used for researching the magneto‐electric manifestation – the electromagneto‐optical (EMO) effect. Magnetic‐field dependencies, the acquired EMO effect, testify to an influence of an external mechanical strain not only on the value of the EMO effect, but also on the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our earlier studies, EMOE was observed in YIG epitaxial films 9, 12, 13. Our experimental techniques as combination of a high‐sensitive laser polarimeter and a polarizing microscope with scanning diaphragm in details described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…In our earlier studies, EMOE was observed in YIG epitaxial films 9, 12, 13. Our experimental techniques as combination of a high‐sensitive laser polarimeter and a polarizing microscope with scanning diaphragm in details described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, garnet films grown on iso-structural substrates with different lattice misfits are generally relaxed above a few tens of nanometers [14]. Linear ME coupling was however observed in quite a few cases of garnet single crystals and epitaxial films [35][36][37][38][39][40]. A large variety of the measurement techniques have been used to detect the effect in different crystallographic directions within garnets of different compositions.…”
mentioning
confidence: 99%
“…The large nuclear charge of Bi leads to the important effect of spin-orbit coupling. More surprising is the presence of linear ME effect in pure and supposedly stoichiometric yttrium iron garnet [35,36,39,42]. Among the explanations, the triclinic YIG symmetry below 130 K [39] or the presence of defects, especially oxygen vacancies [31,42], are discussed.…”
mentioning
confidence: 99%